Managing the Interference for Down-Link in LTE Using Fractional Frequency Reuse - Ibrahim, Ahmed; Al-Awamry, A.Al-Awamry; Mohra, Ashraf Shawky (Indonesian Journal of Science and Technology, 2020)
Long Term Evolution has developed a new radio technology called femtocell or Femto Base station, which is well-suited to improve cellular network capacity and mobile coverage to indoor user's areas. Providing additional capacity and coverage expansion through FBSs could lead to large interference in a cellular radio communication network. In this paper, we proposed an efficient resource allocation scheme based on Fraction Frequency Reuse (FFR) for interference mitigation, where the entire spectrum is shared among network entities. FFR mechanism aims to reduce co-tier and cross-tier downlink interferences by allocating non-overlapping sets of bands to the user equipment at different geographic locations. The main purpose of this work is to compare two main types of FFR schemes, respectively, Strict FFR and Soft Frequency Reuse with the proposed scheme. The three types of FFR schemes were explained and evaluated with Monte-Carlo simulation based on some performance metrics, namely, sum-rate, spectral efficiency, and outage probability. Simulation results showed that the impacts of the proposed scheme are significantly high in comparison with two other methods. The proposed scheme proved to enhance spectral efficiency, reduced the outage probability, and increased the sum rate for all the users.